2010
DOI: 10.1590/s0036-36342010000800016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of cigarette package health warning labels: a cross-country comparison in Brazil, Uruguay and Mexico

Abstract: Objective To assess the impact of different health warning labels (HWL). Material and Methods Data from the International Tobacco Control Survey (ITC Survey) were analyzed from adult smokers in Brazil, Uruguay and Mexico, each of which used a different HWL strategy (pictures of human suffering and diseased organs; abstract pictorial representations of risk; and text-only messages, respectively). Main outcomes were HWL salience and cognitive impact. Results HWLs in Uruguay (which was the only country with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 20 publications
(17 reference statements)
8
80
2
2
Order By: Relevance
“…All indicators of warning salience, and of cognitive and behavioral responses to the warnings significantly increased at the first postimplementation (Wave 2) period compared to the preimplementation (Wave 1) period. These results are similar to those found in ITC studies investigating the effectiveness of warnings in high-income countries, such as Australia (Borland et al, 2009a) and Canada (Hammond et al, 2003), as well as in the few middle-income countries where PHWs have been evaluated, including Thailand (Yong et al, 2013), Malaysia (Fathelrahman et al, 2010), and Mexico (Thrasher et al, 2007(Thrasher et al, , 2010. The common finding that PHWs are more effective than text-only warnings demonstrates the generalizability of the power of graphically depicting the health consequences of tobacco use on warnings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…All indicators of warning salience, and of cognitive and behavioral responses to the warnings significantly increased at the first postimplementation (Wave 2) period compared to the preimplementation (Wave 1) period. These results are similar to those found in ITC studies investigating the effectiveness of warnings in high-income countries, such as Australia (Borland et al, 2009a) and Canada (Hammond et al, 2003), as well as in the few middle-income countries where PHWs have been evaluated, including Thailand (Yong et al, 2013), Malaysia (Fathelrahman et al, 2010), and Mexico (Thrasher et al, 2007(Thrasher et al, , 2010. The common finding that PHWs are more effective than text-only warnings demonstrates the generalizability of the power of graphically depicting the health consequences of tobacco use on warnings.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, a study comparing the impact of Mexican text-only warnings with Canadian PHWs found that warnings in the form of prominent graphic imagery were more effective in improving smoking-related knowledge and in motivating cessation (Thrasher, Hammond, Fong, & Arillo-Santillán, 2007). These results were consistent with a later study conducted among smokers in Brazil, Uruguay, and Mexico, which found that compared to text-only warnings, PHWs depicting smoking-related bodily harm or human suffering were most effective (Thrasher et al, 2010).…”
Section: Introductionsupporting
confidence: 74%
“…It is important to highlight for instance the use of emotionally powerful images on cigarette packages illustrating the negative physical impacts or human suffering due to smoking, combined with the free telephone counseling service, which have a great cognitive impact with smokers with lower educational levels 3,12,24 . On the other hand, it has been reported that individuals with lower educational levels are less aware of anti-smoking propaganda broadcast on television 3 , even though almost 100% of households have a television 25 .…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the methods used by the ITC Brazil Survey have been published elsewhere 12 . The household contact rate was 31.7%, as 68.3% of telephone lines were either not in service, non-residential, fax lines, or in vacant houses.…”
Section: Methodsmentioning
confidence: 99%
“…6 Health warnings constitute a powerful intervention for increasing knowledge about the specific harms of tobacco use 7 and for increasing thoughts and motivations to quit smoking among smokers in many countries including Thailand, Malaysia, Uruguay, Mauritius, Mexico, Australia and Canada. [8][9][10][11][12][13][14] Health warnings also have the potential to prevent smoking initiation among nonsmokers, including youth. 15 Smokers rate health warnings on cigarette packages as a prominent and credible source of information about the harms of tobacco use.…”
Section: Introductionmentioning
confidence: 99%